Effects of Quran Recitation on Heart Rate Variability as an indicator of Student Emotions - Ghanem, Eman; Muhammad Nubli, Abdul Wahab (Human Resource Management Academic Research Society (HRMARS), 2018)
This study examined the effects of Quran recitation on the Heart Rate Variability (HRV) of students. By doing so, this research extends previous findings on the effects of religious activities on university students. This research therefore studies the relationship between HRV with different Quran recitation types with different reading styles (Tajweed), Surah (stories) and themes (i.e. heaven, hell and punishment). The experiment comprises four sessions that each lasted approximately 30 minutes and that involved the recitation of certain Quran Surah or verses. At the end of each session, the difference between pre-and post-session HRVs was derived. The results of this research may be used to help university students reduce stress, tension and anxiety.